ER-associated degradation regulates Alzheimer's amyloid pathology and memory function by modulating γ-secretase activity. Issue 1 (December 2017) - Zhu, Bing; Jiang, LuLin; Huang, Timothy; Zhao, Yingjun; Liu, Tongfei; Zhong, Yongwang; Li, Xiaoguang; Campos, Alexandre; Pomeroy, Kenneth; Masliah, Eliezer; Zhang, Dongxian; Xu, Huaxi
Abstract Endoplasmic-reticulum-associated degradation (ERAD) is an important protein quality control system which maintains protein homeostasis. Constituents of the ERAD complex and its role in neurodegeneration are not yet fully understood. Here, using proteomic and FRET analyses, we demonstrate that the ER protein membralin is an ERAD component, which mediates degradation of ER luminal and membrane substrates. Interestingly, we identify nicastrin, a key component of the γ-secretase complex, as a membralin binding protein and membralin-associated ERAD substrate. We demonstrate a reduction of membralin mRNA and protein levels in Alzheimer's disease (AD) brain, the latter of which inversely correlates with nicastrin abundance. Furthermore, membralin deficiency enhances γ-secretase activity and neuronal degeneration. In a mouse AD model, downregulating membralin results in β-amyloid pathology, neuronal death, and exacerbates synaptic/memory deficits. Our results identify membralin as an ERAD component and demonstrate a critical role for ERAD in AD pathogenesis. Endoplasmic-reticulum associated degradation (ERAD) regulates protein homeostasis. Here the authors identify an ERAD component membralin, and show that it interacts with a member of the γ-secretase complex to regulate β-amyloid (Aβ) pathology and memory deficits in an Alzheimer's disease model.